Probing the beam‐induced heating effect inside a transmission electron microscope by nanoparticle labels. (20th April 2021) - Zhang, Lei; He, Longbing; Yang, Yufeng; Hong, Hua; Tang, Luping; Sun, Litao
Abstract: Beam‐induced heating effect on nanoscale samples is a crucial question, as it strongly influences the interpretation of observed unusual behaviours. This question is currently under debate without a convincing conclusion. Here, using silver nitride (Ag3 N) nanoparticles as temperature labels, we perform an investigation on this heating effect inside a transmission electron microscope (TEM) under normal imaging conditions. Combined with experimental measurements and semi‐quantitative calculations, a temperature increase of more than 100 K is estimated and confirmed in the graphite carbon nitride (g‐C3 N4 ) films. Strong temperature gradients are found to exist in the single‐end fixed g‐C3 N4 films. The influencing factors of heat accumulation are also investigated and discussed. Findings in this study may shed some light on the understanding of the abnormal behaviours of nano‐objects observed inside TEM.